Does Burnout Due to COVID-19 Affect Resilience? The Sample of Doctors in Turkiye - Aziz Bulut; Aliye Bulut; Çağla Yiğitbaş (Genel Tıp Dergisi)
Objective: The consequences of the coronavirus pandemic on doctors are significant. This study was conducted to determine the resilience or burnout status of physicians, the characteristics that make a difference on them and whether burnout predicts resilience. Method: The study was conducted with a quantitative method and a general survey model. 246 physicians were reached in the descriptive cross-sectional study. The volunteers with ethical permission were ensured to be able to answer all questions before collecting the data obtained with the principle of voluntary participation. Results: It has been determined that the age range, income perception, whether they like their profession or not, and whether they are satisfied with the unit they work in are the variables that make a difference in the levels of resilience and burnout of physicians. Self-efficacy, family and social network, coping, and adaptation scores of the physicians in the study were above average in terms of their resilience. Personal achievement and satisfaction with the unit they work predict resilience. Conclusion: In order to increase the resilience of doctors in extraordinary conditions such as pandemics, conditions such as ensuring that they are satisfied with their workplace and supporting their personal success should be created.